2016
DOI: 10.1007/164_2016_30
|View full text |Cite
|
Sign up to set email alerts
|

Delta Opioid Pharmacology in Relation to Alcohol Behaviors

Abstract: Delta opioid receptors (DORs) are heavily involved in alcohol-mediated processes in the brain. In this chapter we provide an overview of studies investigating how alcohol directly impacts DOR pharmacology and of early studies indicating DOR modulation of alcohol behavior. We will offer a brief summary of the different animal species used in alcohol studies investigating DORs followed by a broader overview of the types of alcohol behaviors modulated by DORs. We will highlight a small set of studies investigatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 191 publications
0
6
0
Order By: Relevance
“…Several studies have shown that activation of δOPs can modulate alcohol intake (Alongkronrusmee, Chiang, & van Rijn, 2016) and thus, a synthetic opioid that preferentially activates δOP could minimize the impact of μOP-mediated reward and κOP-mediated aversion on the behavioural effects in the alcohol assays. Indeed, our characterization revealed that MP102 had the desired in vitro pharmacological profile of a G protein-biased, δOP-preferring agonist.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that activation of δOPs can modulate alcohol intake (Alongkronrusmee, Chiang, & van Rijn, 2016) and thus, a synthetic opioid that preferentially activates δOP could minimize the impact of μOP-mediated reward and κOP-mediated aversion on the behavioural effects in the alcohol assays. Indeed, our characterization revealed that MP102 had the desired in vitro pharmacological profile of a G protein-biased, δOP-preferring agonist.…”
Section: Discussionmentioning
confidence: 99%
“…Opioid receptors are expressed in multiple CNS regions, including reward and emotion-related brain structures [ 122 ]. In addition to their well-known antinociceptive effects, opioid receptors are known to play a role in the mechanisms of drug abuse [ 123 ] and alcohol addiction [ 124 ]. There is also some evidence on involvement of opioid receptors in the mechanisms of antidepressant drug action [ 125 ].…”
Section: Palmitoylation Of G Protein-coupled Receptors (Gpcrs)mentioning
confidence: 99%
“…Considering that DORs play a role in mood disorders such as depression and anxiety [113,134] and that depression-like and anxiety-like behaviors are comorbid with AUD [135], the role of DORs in alcohol addiction has been investigated as a potential target for treatment of AUD. It has been suggested that acute and chronic alcohol exposure can affect the expression, pharmacology, and function of DORs [136,137]. For instance, prolonged alcohol exposure using two-bottle limited access [138] or alcohol-induced conditioned place preference (CPP) procedures increased expression of DORs [139].…”
Section: Dorsmentioning
confidence: 99%